2020
DOI: 10.1044/2020_persp-20-00182
|View full text |Cite
|
Sign up to set email alerts
|

Capturing a Moment in Time: A Survey of School-Based Speech-Language Pathologists' Experiences in the Immediate Aftermath of the COVID-19 Public Health Emergency

Abstract: Purpose Data collected by the American Speech-Language-Hearing Association in the spring of 2020 showed that most speech-language pathologists (SLPs) experienced a moderate to major impact on their work practices as a result of the COVID-19 public health emergency. This study focused on gaining a deeper understanding of the experiences of school-based SLPs at this unique moment in time. Method This study involved a survey of 280 school-based SLPs workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 6 publications
6
43
0
Order By: Relevance
“…As pandemic conditions continue, it is critical to examine how SLPs addressed the challenge of swift school closures to identify the types of supports SLPs may require should closures re-occur. Some recent studies of clinical practice and education services highlight the importance of examining these challenges (Garbe et al, 2020;Sylvan et al, 2020). The present study advances this work by addressing the following questions with a very large and nationally-representative sample of SLPs…”
Section: Purpose Of the Current Studymentioning
confidence: 71%
See 2 more Smart Citations
“…As pandemic conditions continue, it is critical to examine how SLPs addressed the challenge of swift school closures to identify the types of supports SLPs may require should closures re-occur. Some recent studies of clinical practice and education services highlight the importance of examining these challenges (Garbe et al, 2020;Sylvan et al, 2020). The present study advances this work by addressing the following questions with a very large and nationally-representative sample of SLPs…”
Section: Purpose Of the Current Studymentioning
confidence: 71%
“…Perhaps more relevant to the present study, however, is that data from Tucker's (2012) survey indicated a negative correlation between SLPs' years of experience and interest in using teletherapy, such that SLPs with 25þ years of experience were less interested in using teletherapy compared to SLPs with only 1-5 years of experience. Very recently, a study surveying school-based SLPs' challenges during the COVID-19 pandemic revealed that only 9% of respondents (n ¼ 280) had ever provided services via teletherapy prior to the pandemic (Sylvan et al, 2020). As such, in the present study, we determine whether the use of teletherapy during the COVID-19 school closures differed according to SLPs years of experience.…”
Section: Teletherapy For School-age Children Prior To Covid-19mentioning
confidence: 92%
See 1 more Smart Citation
“…More recently, SLPs have reported that lack of time to provide optimal service delivery has become an ethical challenge over the last 3 years (ASHA, 2020a). Presently, the COVID-19 pandemic has heightened many of those stressors SLPs experience when working in the schools, as well as higher levels of stress in their personal lives (Sylvan et al, 2020). It is important for school-based SLPs to be aware of what burnout symptoms look like and how they can make small changes at the work level to avoid it.…”
Section: Stressors In the School Settingmentioning
confidence: 99%
“…This has become particularly true during the COVID-19 pandemic, with recent reports indicating that obstacles related to COVID-19 are negatively associated with job satisfaction (Farquharson et al, under review). Service delivery models are changing hastily, workload responsibilities are increasing, and concerns for one's overall well-being are heightened during this time (Sylvan et al, 2020). Since large scale changes (e.g., policy change at a national level) cannot happen instantaneously, there is a call for gradual, habitual changes in our daily work setting to help mitigate occupational stress.…”
mentioning
confidence: 99%